2021
DOI: 10.1149/1945-7111/ac1a85
|View full text |Cite
|
Sign up to set email alerts
|

Review—Use of Impedance Spectroscopy for the Estimation of Li-ion Battery State of Charge, State of Health and Internal Temperature

Abstract: The rapid adoption of electric vehicles (EVs) and the evolving needs of portable electronic devices has intensified the need for enhanced state diagnosis of Li-ion batteries (LIBs). As the applications for LIBs continue to grow, so too does their operational requirements; ranging from faster charging and improved safety to optimized energy control and extended lifespan. In order to keep pace with the growing requirements of LIBs, improvements in the monitoring of battery states must be achieved. Although elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 228 publications
(478 reference statements)
0
39
0
Order By: Relevance
“…Each different type of method has its advantages and limitations 53–57 . Therefore, a summary of all the prominent techniques would be very helpful to researchers and developers serving as a baseline for further research and as a guideline for selecting appropriate techniques suitable for a specific requirement 58–62 . However, such a summary with detailed discussion on current progress and explanation of the principles, applications, challenges, and future research scopes has not yet been presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each different type of method has its advantages and limitations 53–57 . Therefore, a summary of all the prominent techniques would be very helpful to researchers and developers serving as a baseline for further research and as a guideline for selecting appropriate techniques suitable for a specific requirement 58–62 . However, such a summary with detailed discussion on current progress and explanation of the principles, applications, challenges, and future research scopes has not yet been presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55][56][57] Therefore, a summary of all the prominent techniques would be very helpful to researchers and developers serving as a baseline for further research and as a guideline for selecting appropriate techniques suitable for a specific requirement. [58][59][60][61][62] However, such a summary with detailed discussion on current progress and explanation of the principles, applications, challenges, and future research scopes has not yet been presented in the literature. Therefore, this article covered the research gap by conducting a comprehensive review of the state-of-theart temperature prediction strategies using EIS reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the external temperature of the cell packaging can remain essentially unchanged for a time interval that can be too long for early detection of the event [24,25]. Since standard temperature sensors such as thermo-couples and thermoresistors, even if characterized by relative low cost and sufficient accuracy [26], are difficult to integrate into Li-ion cells to measure the internal temperature, approaches based on the measurement of internal impedance [27,28] and electro-thermal models are emerging [29]. Recently, thanks to the miniaturization and price decrease of printed circuit boards (PCBs), EIS measurement can also be adopted online, with no need of turning the battery pack off.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, besides SOH estimation, the root causes of capacity fade can also be quantified and the impact on ageing of operating conditions, such as temperature, cycling depth or current, can be better understood. However, the practical utilisation of mechanistic models depends on resource-intense parameterisation [13,14], and due to model complexity, the operation and fitting of the models may not be rapid [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…EIS is especially useful for analysing the internal state of the cellin particular, the interfacial properties that evolve as the cell ages. Efforts to date on SOH prediction using EIS have been reviewed comprehensively by Mc Carthy et al [16], including online estimation challenges. One simple approach is the direct correlation of a spectral feature with cell degradation.…”
Section: Introductionmentioning
confidence: 99%